Hestnes Ferreira’s proposal for Amsterdam city hall competition − analyzed in continuity with Louis Kahn - Saraiva, A. (2021)
The end of the modern movement and the definitive realization of postmodernism installed a period of transition, full and diverse interpretations that overlap with new rationalities and build new ways of problematizing architecture, in the late 1960s. In 1967, the municipality of Amsterdam organized an international competition for its new City Hall. This competition corresponds to a critical moment for the internationalization of Portuguese architects during the period of the Portuguese dictatorship. The analysis focuses only on the proposal of the architect Hestnes Ferreira, who studied and worked with Louis Kahn. The analysis carried out on the project highlights the formal links between the two architects: the interpretation of the concept of Institution; the large central space and the entrance; the order or hierarchy of spaces; served spaces, servant spaces; materiality; natural light; and, finally, monumentality. The objective of this article is to show how Hestnes Ferreira’s proposal projects in continuity with Louis Kahn. This article is part of the ongoing Postdoctoral research (2015−2021).